O Programa Residência Pedagógica em tempos de pandemia na perspectiva dos residentes de Pedagogia da Universidade Federal de Alfenas - MG - Polita, Leandra Borges (2023)
The Pedagogical Residency Program (PRP) is an action of the National Policy for Teacher Training, developed by the Ministry of Education and the Coordination for the Improvement of Higher Education Personnel, in partnership with Higher Education Institutions, which have degrees, and Basic Education Schools, aiming to improve the theoretical-practical training of residents, from the second half of the course. This study aims to understand the development of PRP at the Federal University of Alfenas - MG (UNIFAL-MG), in the context of the pandemic, from the perspective of the residents of the Pedagogy course, as well as to identify the implications of this reality in teacher education. The study covers the theoretical reference on teacher training; the context that refers to the legal devices of the Teacher Training Policy in Brazil and the PRP at national and institutional level; the analysis of an on-line questionnaire, which is part of a larger research, entitled "The Pedagogical Residency Program in the context of the COVID-19 pandemic", coordinated by PhD Teacher Helena Maria dos Santos Felício, aiming at the search for information about the profile of training and professional activity of the residents of the Pedagogy course; and semi-structured interviews on the development of the PRP at UNIFAL-MG during the pandemic. The methodological assumptions of this research are constituted through the historical-dialectical perspective in an understanding and qualitative synthesis of the data and speeches of the subjects in real context. The research indicates that public policies for teacher education are not static, they follow the social, cultural, historical and political movement; that the PRP due to the complexity of the dimensions attributed by the implementation context may establish changes in the initial proposal at a microstructural level; that with the pandemic the development of the PRP adapts to new forms of on-line interaction; that theory and practice in the teaching professional learning process integrate each other; that Information and Communication Technologies are relevant in initial training; that there is a displacement of the school's locus to the homes of those involved; that with virtual contact in the PRP arises many anxieties, but also successes; that during the pandemic there is a virtual improvisation and minimal immersion in the school context in the PRP; and that teacher training should be continuous.